Transformation of Kebun Kelapa Village Administration with Platform as a Service (PaaS) Cloud Computing - Fachrid Wadly; Akhyar Lubis; Nova Mayasari; Ricky Fernando Ginting; Rizky Ananda Pratama (Yayasan Sinergi Multidimensi Kreatif, 2024)
Villages, as the smallest part of the government administration system in Indonesia, are required to be able to follow technological developments and continue to improve their ability to manage village population administration data. Currently, the village is in the administrative service system. The villagers are still conventional; this affects village devices and villagers, where human error is common, as well as waste of time and costs. So it takes the use of the right technology to overcome this. Cloud computing is a paradigm that allows users to access information electronically using fixed devices or mobile devices connected to the internet network. Cloud computing offers PaaS (Platform as a Service) collaboration, on-demand services,and anytime, anywhere access capabilities. With cloud computing, digital village systems can be built. To be able to use the service, the village government must first subscribe to a cloud service provider.Based on the test results, it can be concluded that the implementation of Kebun Kelapa Village administration provides convenience in processing village population data, reduces village operational costs, and can provide more optimal administrative services to villagers, especially Kebun Kelapa.